DISKRIMINASI TOKOH UTAMA PEREMPUAN DALAM NOVEL SAYAP-SAYAP RUH KARYA PRAHARA PUTRA (KRITIK SASTRA FEMINISME EKSISTENSIALIS) - Amalia Agustin Nuryanti; Afriani Ulya; Nurlailatul Qadriani (Seshiski: Southeast Journal of Language and Literary Studies, 2025)
This study analyzes the forms of discrimination against the character Ismi in the novel Sayap-Sayap Ruh by Prahara Putra using Simone de Beauvoir’s existentialist feminism approach. The research aims to identify the discrimination attached to Ismi. A qualitative analysis method is used to examine the forms of discrimination against Ismi in the novel. The findings show that Ismi experiences gender discrimination in the form of marginalization, including: 1) pressure to have children, 2) neglect of personal life, 3) women being considered deviant, and 4) neglect of emotional experiences. Ismi also experiences subordination in the form of: 1) prioritizing others’ interests, 2) lack of the right to refuse, 3) feelings being considered invalid, and 4) double burden. Ismi experiences stereotypes such as: 1) lack of emotional stability, 2) tendency to be spoiled, 3) role as a mother, and 4) recognition and irony.